Optimization of Sugar Production from Oil Palm Empty Fruit Bunch by Cellulase from Aspergilus niger C-1184 - Wangsirikul, Piyaporn; Wangsirikul, Teerapat (Princess of Naradhiwas University Journal, 2020)
This research investigated sugar production from oil palm empty fruit bunch. The steam explosion assisted with 3 M NaOH for 30 minutes was used for pretreatment. After pretreatment, the chemical content of pretreated fiber contained 83.73% cellulose 92.33% holocellulose and 19.33% lignin. In fact, raw material before pretreatment contained 78.22% cellulose 97.78% holocellulose and 27.00% lignin. Then the morphology of treated and untreated fiber were brought to observe by Field Emission Scanning Electron Microscopy Analysis (FE-SEM). It found that there were significant differences in the fiber surface morphology for both treated and untreated oil palm empty fruit bunch. The untreated oil palm empty fruit bunch had a smooth surface while the pretreatment ones had a porous surface. In this study, the oil palm empty fruit bunch was converted into sugar by hydrolysis oil palm empty fruit bunch with 10 mg/ml cellulose from Aspergilus niger C-1184. With 30 g of pretreated oil palm empty fruit bunch, It took 12 hours to process which were able to convert into sugar 14088.33 µg/ml. In addition, the sugar was tested by High-Performance Liquid Chromatography (HPLC), it appeared to be glucose.